Targeting PD-1/PD-L1 inhibits rejection in a heterotopic tracheal allograft model of lung transplantation - Kaiho, Taisuke; Suzuki, Hidemi; Hata, Atsushi; Matsumoto, Hiroki; Tanaka, Kazuhisa; Sakairi, Yuichi; Motohashi, Shinichiro; Yoshino, Ichiro (Frontiers in Pharmacology, 2023)
Immune checkpoint molecules such as programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) have revolutionized the field of lung cancer treatment. As part of our study, we examined the role of these proteins in acute rejection in a mouse model of heterotopic tracheal transplantation. Recipient mice were untreated (Allo group) or treated with anti-PD-L1 (aPDL1 group) or PD-L1 Fc recombinant protein (PD-L1 Fc group). A further group of C57BL/6 mice received isografts (Iso group). The occlusion rate was significantly higher in the Allo group than in the Iso group (p=0.0075), and also higher in the aPD-L1 group (p=0.0066) and lower in the PD-L1 Fc group (p=0.030) than in the Allo group. PD-L1 Fc recombinant protein treatment significantly decreased interleukin-6 and interferon-γ levels and reduced the CD4 + /CD8 + T cell ratio, without increasing PD-1 and T-cell immunoglobulin mucin 3 expression in CD4 + T cells. These data suggest that PD-L1 Fc recombinant protein decreases the levels of inflammatory cytokines and the proportion of CD4 + T cells without exhaustion. The PD-L1-mediated immune checkpoint mechanism was associated with rejection in the murine tracheal transplant model, suggesting a potential novel target for immunotherapy in lung transplantation.